Agriculture and the new industrial revolution in Asia - Bautista, Romeo M.; DeRosa, Dean A. (International Food Policy Research Institute, 1996)
This paper examines the role of agriculture and rural development, in general, in the most successful countries of Asia, termed, by the World Bank, the East Asian Miracle. The basic hypothesis of the paper is that agricultural growth and rural development play a vital role in the sustained industrialized and economic growth of many Asian countries that are still heavily agricultural. The authors explore the hypothesis both conceptually and quantitatively and refer to certain key features of Asian-country experiences.